2020
DOI: 10.1021/acs.joc.0c01244
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Strategy for Diastereocontrolled Synthesis of Small- and Medium-Ring Architectures

Abstract: Nitrogen and oxygen medium rings, in particular nine-membered rings, epitomize a unique area of chemical space that occurs in many natural products and biologically appealing compounds. The scarcity of 8- to 12-membered rings among clinically approved drugs is indicative of the difficulties associated with their synthesis, principally owing to the unfavorable entropy and transannular strain. We report here a scandium triflate-catalyzed reaction that allows for a modular access to a diverse collection of nine-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Seventy compounds [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] with diverse scaffolds from our in-house pilot compounds library were initially screened to identify potential inhibitors of PLpro at a single concentration of 10 μg/mL using PLpro enzymatic inhibition assay (BPS Bioscience, San Diego, CA, USA). A PLpro inhibitor, GRL-0617, was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventy compounds [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] with diverse scaffolds from our in-house pilot compounds library were initially screened to identify potential inhibitors of PLpro at a single concentration of 10 μg/mL using PLpro enzymatic inhibition assay (BPS Bioscience, San Diego, CA, USA). A PLpro inhibitor, GRL-0617, was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a phenotypic screen was performed using in-house developed compound collection [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] to identify PLpro inhibitors using fluorescence resonance energy transfer (FRET)-based assay. The screening revealed that out of the 70 tested compounds, 13 exhibited over 50% inhibitory activity at a concentration of 10 μg/mL (Supp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure of keto lactams 32 and 28 to triethylamine or aq. NaOH in ethanol , at room temperature (rt) afforded quinolones 38 and 39 in yields of 77 and 80%, respectively (Table ). Finally, the known compounds 2 , ,, 3 , , 4 , ,, 5 , and 12 were synthesized by published procedures.…”
Section: Resultsmentioning
confidence: 99%